COVID-19 in a cohort of pregnant women and their descendants, the MOACC-19 study - Jessica Alonso-Molero; Javier Llorca; Carolina Lechosa-Muñiz; Pilar Gortazar; María Fernández-Ortiz; Yolanda Jubete; Maria J Cabero; Bárbara Arozamena; Laura Conde-Gil; Elsa Cornejo del Río; Rocío Cuesta-González; Trinidad Dierssen-Sotos; et al. (BMJ Open)
Purpose The Mother and Child COVID-19 study is a cohort recruiting pregnant women and their children in Cantabria, North of Spain, during COVID-19 pandemic in order to ascertain consequences of SARS-CoV-2 infection on pregnant women and their descendants. This article reports the cohort profile and preliminary results as recruitment is still open.Participants Three subcohorts can be identified at recruitment. Subcohort 1 includes women giving birth between 23 March and 25 May 2020; they have been retrospectively recruited and could have been exposed to COVID-19 only in their third trimester of pregnancy. Subcohort 2 includes women giving birth from 26 May 2020 on; they are being prospectively recruited and could have been exposed to COVID-19 in both their second and third trimesters of pregnancy. Subcohort 3 includes women in their 12 week of pregnancy prospectively recruited from 26 May 2020 on; they could have been exposed to COVID-19 anytime in their pregnancy. All women are being tested for SARS-CoV-2 infection using both RT-PCR for RNA detection and ELISA for anti-SARS-CoV-2 antibodies. All neonates are being tested for antibodies using immunochemoluminiscency tests; if the mother is tested positive for SARS-CoV-2 RNA, a nasopharyngeal swab is also obtained from the child for RT-PCR analysis.Findings to date As of 22 October, 1167 women have been recruited (266, 354 and 547 for subcohorts 1, 2 and 3, respectively). Fourteen women tested positive to SARS-CoV-2 RNA by the day of delivery. All 14 children born from these women tested negative for SARS-CoV-2 RNA.Future plans Children from women included in subcohort 3 are expected to be recruited by the end of 2020. Children will be followed-up for 1 year in order to ascertain the effect that COVID-19 on their development.